Understanding Patient Preferences: A Review of Patient-Centred Approach in Hospital Ward Interior Design - Adelita, Syifa Diella; Astuti, Susy Budi (Technium Social Sciences Journal, 2024)
Patients who seek treatment in hospitals have a unique conditions that should be considered in facility design. Facilities that are not designed according to the patient’s needs and preferences give rise to the phenomenon of discomfort in the process of treatment at the hospital. Interior is one aspect of the built environment that plays a role in patient preferences. This study aims to examine patient preferences in hospital ward interiors to create a comprehensive understanding of patient preferences for a hospital ward. The study conducted by literature studies and through participants validation questionnaire from Indonesia. The results of the study show patients’ preferences for interiors that can accommodate the comfort, security, safety, and social needs of patients during inpatient treatment. Preference for interior aspects related to natural elements is also often found in the research results.